Expanding Occupational Therapy Perspectives with Family Caregivers. (September 2022) - Demers, Louise
Abstract: Background . Family caregivers are ever-present and crucial collaborators in the work of occupational therapists but are rarely the focus of their efforts.Purpose . This lecture will discuss the greater inclusion of family caregivers in occupational therapy and the exciting possibilities that emerge from this change.Key issues . Family caregivers are a unique client population. This position statement is supported by recent research on occupational therapists' values and shifts towards an occupational participation approach in the profession. Working with this client population requires a nuanced understanding of their experience. Caregiving can be burdensome, but it can also create positive effects many of which can be identified and understood through a relational lens.Implications . Through a three-fold approach, occupational therapists can work with caregivers to locate and mitigate negative caregiving effects, discover, and build on positive effects, and further develop positive outcomes by encouraging and balancing caregiving and non-caregiving occupations.